Lack of Influence of Skeletal Muscle Mass on the Determination of the Risk of Falling of self-reliant elderly Persons with functional Limitations - Gotthardt, Susann; Franke, Anna; Auerswald, Tina; Kraska, Carolin; Mellou, Marina; Hofmann, Anne; Reith, Veronika; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)

Laying the foundation for a core set of the International Classification of Functioning, Disability and Health for community-dwelling adults aged 75 years and above in general practice: a study protocol - Tomandl, Johanna; Book, Stephanie; Gotthardt, Susann; Heinmüller, Stefan; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Hoyer, Stefanie (BMJ Open, 2018)
Introduction With the medical focus on disease, the problem of overdiagnosis inevitably increases with ageing. Considering the functional health of patients might help to discriminate between necessary and unnecessary medicine. The International Classification of Functioning, Disability and Health (ICF) is an internationally recognised tool for describing functional health. However, it is too detailed to be used in primary care practices. Consequently, the aim of this study is to identify relevant codes for an ICF core set for community-dwelling older adults (75 years and above) in primary care. Methods and analysis The study will follow the methodology proposed by the ICF Research Branch to identify relevant concepts from different perspectives: (1) Research perspective: A systematic review of studies focusing on functional health in old age will be conducted in different databases. Relevant concepts will be extracted from the publications. (2) Patients' perspective: Relevant areas of functioning and disability will be identified conducting qualitative interviews and focus groups with community-dwelling older persons. The interviews will be transcribed verbatim and analysed using the documentary method of interpretation. (3) Experts' perspective: An online survey with open-ended questions will be conducted. Answers will be analysed using the qualitative content analysis of Mayring. (4) Clinical perspective: A cross-sectional empirical study will be performed to assess the health status of community-dwelling older adults using the extended ICF checklist and other measurement tools. Relevant concepts identified in each study will be linked to ICF categories resulting in four preliminary core sets. Ethics and dissemination Ethical approval for the study was obtained (90_17B). All participants will provide written informed consent. Data will be pseudonymised for analysis. Results will be disseminated by conference presentations and journal publications. Trial registration number Projektdatenbank Versorgungsforschung Deutschland: VfD_17_003833, Clinicaltrials.gov: NCT03384732 and PROSPERO: CRD42017067784.
EVALuna2:35588

Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: Relevant categories of their functioning from the research perspective, a scoping review - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann (BMJ Open, 2021)
Objectives The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting Home, primary care. Participants Community-dwelling adults aged 75 years and above. Results From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the â € activities and participation' component. The most frequently identified categories were â € memory functions', â € dressing' and â € changing basic body position'. Conclusions This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-05
Keywords: general medicine (see internal medicine); geriatric medicine; primary care

Laying the foundation for an ICF core set for community dwelling older adults in primary care: an expert survey Entwicklung eines ICF-Core-Sets für ältere Patienten in der Hausarztpraxis: eine Expertenumfrage - Gotthardt, Susann; Tomandl, Johanna; Höfle, Anina; Kühlein, Thomas; Book, Stephanie; Graessel, Elmar; Talaska, Michael; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: A holistic biopsychosocial model focused on functioning in individual contexts (environment, task) is better suited to meet the needs of older patients than disease only based models. The International Classification of Functioning, Disability and Health (ICF) is the official standard for describing functional health. As the ICF is too detailed to be used in practice, brief core sets have been developed. Objective: This study aimed to identify relevant aspects of functioning for older primary care patients from the perspective of healthcare professionals in Germany. Material and methods: An internet-based cross-sectional expert survey was conducted in preparation for the development of an ICF core set for community-dwelling patients aged 75 years and older. Open-ended questions to identify the most important aspects of functioning and disability in old age were used. Responses were analyzed based on a content analysis approach to identify relevant concepts in the care of the target population. These concepts were then linked to ICF categories according to established linking rules. Results: A total of 63 experts participated in this survey. Across all responses, 2240 meaningful concepts were identified. A total of 75 ICF categories (4 first level categories, 67 second level categories, 4 code combinations) were identified by at least 5% of respondents and will thus be considered as candidate categories for the final ICF core set. Most of concepts were associated with the environmental factors component. The most frequently identified categories were immediate family and family relationships. Conclusion: This survey provides a list of relevant ICF categories from the experts’ perspective and together with other preparatory studies will be used for developing an ICF core set for community-dwelling older adults in primary care.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Community-dwelling older patients; Expert survey; Functioning; ICF core set; Primary care

Laying the foundation for an International Classification of Functioning, Disability and Health Core Set for community-dwelling elderly adults in primary care: the clinical perspective identified in a cross-sectional study - Book, Stephanie; Ulbrecht, Gudrun; Tomandl, Johanna; Kühlein, Thomas; Gotthardt, Susann; Freiberger, Ellen; Grässel, Elmar (BMJ Open, 2020)
OBJECTIVES: Having more information about the biopsychosocial functioning of their geriatric patients might help physicians better balance medical interventions according to patients' needs. For this reason, we aimed to develop an easy-to-handle International Classification of Functioning, Disability and Health (ICF) Core Set for community-dwelling geriatric patients aged 75 and older in primary care. In this empirical study, we describe the functioning and health of community-dwelling patients aged 75 and older in primary care in Germany and identify the most common problems encountered by these individuals when using the ICF. DESIGN: In this exploratory, cross-sectional study, a health professional conducted semi-structured interviews. SETTING: Community-dwelling older adults aged 75 and older in Germany. PARTICIPANTS: 65 participants (mean age=80.2, SD=3.6). OUTCOME MEASURES: Extended ICF Checklist V.2.1a, patients prioritised chapters of the 'activities and participation' component. RESULTS: The three most common impairments for 'body functions' were visual system functions (ICF-code b210; 89%), blood pressure functions (b420; 80%) and sensations associated with hearing and vestibular functions (b240; 59%). For 'body structures', they were eyes, ears and related structures (s2; 81%), structure of mouth (s320; 74%) and structures related to the digestive, metabolic and endocrine systems (s5; 49%). For the 'activities and participation' component, adequate aids compensated for activity limitations to a certain degree. Still, after having adequate aids, the category in which the participants had the most difficulty was walking (d450; 35%). Participants rated the 'mobility' chapter as the most important of all chapters. 'Environmental factors' were facilitators of participants' functioning. CONCLUSIONS: This empirical study provides a list of ICF categories relevant to older adults from the clinical perspective. Along with lists from the other three preparatory studies, it will form the basis for the development of an ICF Core Set for community-dwelling older adults in primary care. TRIAL REGISTRATION DETAILS: The trial is registered in ClinicalTrials.gov (NCT03384732).
CRIS-Team Scopus Importer:2020-12-04
Keywords: aging; community-dwelling older people; core set; functioning; general practice; ICF

Laying the foundation for a primary care core set of the international classification of functioning, disability and health (icf) for community-dwelling older adults: A qualitative study - Tomandl, Johanna; Book, Stephanie; Höfle, Anina; Grässel, Elmar; Sieber, Cornel; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Gotthardt, Susann (Journal of Rehabilitation Medicine, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring s qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community-dwelling elderly people, which will be used to develop a Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-26
Keywords: aged; cross-sectional study; Disability and Health; focus group; general practice/methods.; geriatric assessment/ methods; independent living; International Classification of Functioning; interviews as topic

Sarcopenia and Physical fRailty IN older people: multi-componentT treatment strategies: Design and Method of the EU Study SPRINTT - Freiberger, Ellen; Schöne, Daniel; Franke, Anna; Gotthardt, Susann; Reith, Veronika; Rempe, Hanna; Sieber-Eckert, Gabrielle; Sieber, Cornel (Internist, 2018)

Validation of the SARC-F as a Screening Tool for the Detection of Sarcopenia in older People with functional Limitations - Auerswald, Tina; Franke, Anna; Gotthardt, Susann; Hofmann, Anne; Kraska, Carolin; Mellou, Marina; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)

Validation of the SARC-F as a Screening Tool for the Detection of Sarcopenia in older People with functional Limitations - Auerswald, Tina; Franke, Anna; Gotthardt, Susann; Hofmann, Anne; Kraska, Carolin; Mellou, Marina; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)